2013
DOI: 10.1097/inf.0b013e318292f425
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Placental Transmission of Maternal Antibodies Specific for Neisseria meningitidis Serogroups A, C, Y and W135 and Influence of Maternal Antibodies on the Immune Response to a Primary Course of MenACWY-CRM Vaccine in the United Kingdom

Abstract: The levels of serogroup-specific meningococcal antibodies were low in mothers and 2-month-old infants. Immunizing mothers before or during pregnancy with meningococcal conjugate vaccines might increase antibody levels in early infancy and provide protection against infection due to N. meningitidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In the same study, there was no consistent impact of maternal antibodies on the immune response of infants to MenACWY-CRM vaccination. Despite a moderate association between MenC hSBA at 2 months and a reduced post-dose 2 MenC hSBA level, 90% of infants achieved protective hSBA titers for MenC after the second MenACWY-CRM dose at 4 months of age [38].…”
Section: B-cell Responses and Impact Of Maternal Antibodies On Vaccinmentioning
confidence: 85%
See 2 more Smart Citations
“…In the same study, there was no consistent impact of maternal antibodies on the immune response of infants to MenACWY-CRM vaccination. Despite a moderate association between MenC hSBA at 2 months and a reduced post-dose 2 MenC hSBA level, 90% of infants achieved protective hSBA titers for MenC after the second MenACWY-CRM dose at 4 months of age [38].…”
Section: B-cell Responses and Impact Of Maternal Antibodies On Vaccinmentioning
confidence: 85%
“…A study of antibody persistence up to 5 years after 4-dose infant primary vaccination showed that around one-half of children continued to have seroprotective hSBA titers (≥1:8) for serogroups W and Y, and 26% for serogroup C, whereas hSBA titers waned rapidly for MenA (6% of children had hSBA ≥1:8 by age 5 years) ( Figure 2) [31]. Persistence of bactericidal [38] UK: United Kingdom; US: United States; DTaP-HBV-IPV: combined diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus vaccine; DTaP-HBV-IPV/Hib: combined hexavalent diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus and Haemophilus influenzae type b conjugate vaccine; MenACWY-TT: quadrivalent meningococcal A, C, E, Y vaccine conjugated to tetanus toxoid; HAV: hepatitis A vaccine;…”
Section: Assessment Of Reactogenicity and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study examining the influence of maternal antibodies specific for serogroups A, C, W, and Y on infant responses to MenACWY‐CRM vaccination at 2 and 4 months of age, maternal antibody levels were low and did not associate with infant vaccine responses. However, immunizing women before or during pregnancy may increase antibody levels and subsequent placental transmission to confer increased protection to the infant …”
Section: Discussionmentioning
confidence: 99%
“…129 Consequently, vaccination of pregnant women with meningococcal vaccines is recommended, if indicated.…”
Section: Vaccination Of Pregnant Womenmentioning
confidence: 99%